APOE-ε4 polymorphism and cognitive deficit among the elderly population of Fernando de Noronha Polimorfismo de APOE-ε4 e déficit cognitivo na população idosa de Fernando de Noronha - Anália Nusya Garcia; Helker Albuquerque da Silva; Renan Carlos Silva; Eliane Maria Medeiros Leal; Lorena Rodrigues; Vanessa Cavalcante da Silva; Edileine Dellalibera; Elizabete Malaquias Freitas; Luiz Ataíde Jr; Maria Tereza Cartaxo Muniz (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Polymorphism of the gene for apolipoprotein E (APOE) is an important risk factor for the development of Alzheimer's disease. The ε4 allele of the APOE gene has been linked with a number of neuropsychiatric illnesses, and also with stress and depression among geriatric populations. OBJECTIVE: To identify APOE-ε4 polymorphism and correlate this with cognitive deficit among the elderly population of the island of Fernando de Noronha. METHOD: Neuropsychiatric tests (mini-mental state examination, verbal fluency test and clock drawing test) were applied to 52 elderly people without Alzheimer's disease. DNA was isolated from peripheral blood and genotyping of APOE was done by the PCR-RFLP method. RESULTS: 87% of the elderly population (mean age 69.6±7.0) had cognitive deficit. CONCLUSION: The observed frequency of the ε4 allele was 10%, but the correlation between the presence of ε4 and cognitive deficit in this population was not statistically significant. INTRODUÇÃO: Polimorfismos no gene da apoliproteína E (APOE) são importantes fatores de risco para o desenvolvimento da doença de Alzheimer (DA). O alelo ε4 do gene APOE tem sido relacionado com declínio cognitivo e algumas doenças neuropsiquiátricas, primariamente a doença de Alzheimer. OBJETIVO: Identificar os polimorfismos de APOE-ε4 e relacionar com deficit cognitivo na população idosa da ilha de Fernando de Noronha. MÉTODO: Foram aplicados testes neuropsiquiátricos (mini exame do estado mental, teste de fluência verbal e teste do relógio) em 52 idosos sem DA. O DNA foi isolado do sangue periférico e a genotipagem de APOE foi realizada por PCR-RFLP. RESULTADOS: 87% da população idosa com idade média de 69.6±7.0 apresentou déficit cognitivo. Foi observada uma freqüência de 10% do alelo ε4. CONCLUSÃO: Não foi encontrada significância estatística quando relacionada a presença deste alelo e déficit cognitivo nos idosos avaliados.